Venom. The last dance [videorecording (Blu-Ray)] - Marcel, Kelly, 1974-; Hardy, Tom, 1977-; Hardy, Tom, 1977-; Deacon, Dan, 1981-; Ejiofor, Chiwetel; Temple, Juno, 1989-; Ifans, Rhys, 1967- (Sony Pictures Home Entertainment, 2025)
Tom Hardy returns as Venom, one of Marvel's greatest and most complex characters, for the final film in the trilogy. Eddie and Venom are on the run. Hunted by both of their worlds and with the net closing in, the duo is forced into a devastating decision that will bring the curtains down on Venom and Eddie's last dance.